The The effect of perceived price, e-trust, and quality of delivery on repurchase intention mediated by perceived value on Tokopedia - Saragih, Reni Harlina; Pasaribu, Lamhot Henry (Institute of Computer Science (IOCS), 2023)
Technological developments have brought major changes, especially shopping behavior in Indonesian E-commerce is increased significantly. This research wants to determine the effect of perceived price, e-trust and quality of delivery by Tokopedia on repurchase intentions mediated by the perceived value. This research uses a quantitative approach through an online survey of 265 sample respondents and analyzed using Smart-PLS version 3.29 software. The results of this research show that perceived price, e-trust and quality of delivery has a positive effect on repurchase intention mediated by the perceived value. As a managerial effect, this research shows whether perceived price, e-trust, quality of delivery are important things for e-commerce companies.